Stressors And Stress Levels Of Primary School Music Teachers In Selangor, Malaysia - Jamaludin, Juriani (2007)

(untitled)
Music teaching in primary schools in Malaysia has been implicated with several challenges to teachers such as managing students’ attitude towards learning music, handling school administrators’ demands, and facing inadequate music facilities. This study was designed to examine the level of stress according to selected stressors experienced by primary school music teachers. The stressors under study were categorized into six subscales which are ‘Student Characteristics’, ‘Teacher Characteristics’, Administrative Procedures’, ‘Social Supports’, ‘Facilities and Equipments’ and ‘Music Syllabus Contents’. This research also attempted to the difference of stress level according to demographic characteristics which are gender, training, music teaching experience and music qualification of the music teachers. The sample of this study consisted of 326 trained and untrained music teachers in Selangor. A questionnaire consists of items of stressors with open ended questions was distributed to the teachers in order to gather data concerning their demographical characteristics and level of stress according selected stressors. The study utilized descriptive statistics to analyze the stress level and t-test to determine the difference of stress level according to demographic characteristics. The responses to open-ended questions were analyzed using frequencies and percentages. The research findings indicate that generally, music teachers in this study were having only mild stress in their teaching and learning music in school. Subscale of ‘Social Supports’ was rated as the main contributor to teachers’ stress whereas ‘Music Syllabus Contents’ was seen as the least source of stress. Among the particular item of stressors, ‘lack of trained music teacher’, ‘lack of music resources and book’, ‘lack of skill in playing musical instrument’, ‘inadequate allocation to buy costume for music performance’ and ‘lack of recognition for music education’ were rated by the teachers as the main source of their stress. With respect to overall stress level, t-test analysis showed no significant difference for all four demographic characteristics. The result, however, indicated that male music teachers felt more stress compared to female music teachers in the subscale of ‘Social Support’. Untrained music teachers, novice music teachers and music teachers without external music qualification experienced more stress than trained teacher, experienced teacher and music teachers with external music qualification in the subscale of ‘Teacher Characteristic’. Meanwhile, experienced music teachers and music teachers with music qualification experienced less stress in facing inadequate facilities and equipments in school compared to those who posses no music qualification and do not have experienced in teaching music in school. This study highlights the importance of social support towards music teaching as the main contributor to music teacher stress in school. In addition, teachers’ training in music need to be emphasized as it greatly helps to instill knowledge and confidence for teachers to teach the subject. Finally, the Ministry of Education must provide adequate facilities and proper equipment for music learning in schools so that the subject can be taught effectively. Recommendation of future study should involve larger and more representative sample groups from different states in order to have more conclusive findings, which could be generalized. Besides that, for further research can include a continued analysis of music teacher stress issues associated with music teaching in a secondary school setting and identification of different stress variables.